PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA PADA MATERI UPAYA PELESTARIAN LINGKUNGAN UNTUK PESERTA DIDIK DI SDN PAGINTUNGAN - Siti Mayuni; Nana Hendracipta; Syachruroji Ahmad (Jurnal Holistika, 2023)
This  research  aims  to  find  out  how  to  develop  diorama  learning  media  on environmental preservation material for class V students at SDN Pagintungan, to find  out  the  feasibility  of  the  diorama  learning  media  that  researchers  have developed,  and  to  find  out  students'  responses  to  diorama  learning  media.  This research was conducted at Pagintung Elementary School with 20 class V students as research subjects. This type of research refers to the Borg & Gall development model  which  was  then  modified  by  Sugiyono  which  consists  of  7  stages,  namely problem  analysis,  data  collection,  product  design,  design  validation,  design revision,  product  testing  and  final  results.  The  instruments  used  are questionnaires for product validation by a team of experts (media, materials and educators) and student response questionnaire sheets. Based on data analysis, it can be concluded that the diorama learning media for training understanding of material  on  environmental  conservation  efforts  for  class  V  students  at  SDN Pagintungan that has been developed is in the Very Appropriate category with a percentage  of  91.3%  from  media  experts,  the  Very  Appropriate  category  with  a percentage of 99.3% from material experts and the Very Eligible category with a percentage  of  95%  from  expert  educators.  The  students'  response  to  diorama learning  media  in  the  trial  with  20  respondents  was  93%  included  in  the  Very Good category